'What did I get myself into?' Indigenous women and mining employment in Australia. (December 2022) - Parmenter, Joni; Drummond, Florence
Highlights: Overlapping oppressions create different experiences of mining work. Negative experiences of mining work can be compounded for Indigenous women. Industry has little guidance on how to manage the intersection between gender and race. Employment data for Indigenous women is not reported, rendering this cohort invisible. The findings offer insights for future policy and practice. Abstract: The prevailing view in the literature is that women are more adversely impacted by mining than men, with a major contributing factor being that women are largely excluded from accessing the benefits of employment at large scale operations. Despite industry efforts to increase female participation over the past decade or so, the mining industry remains male dominated. Very few studies provide any substantial employment data on Indigenous women or detail their experience working at large mines. This article presents an overview of recent developments for Indigenous women employed in the Australian resource industry, and their experiences, drawing on research conducted at four large mines in Western Australia. The authors argue that the industry is not adequately recognising or responding to gender-based employment impacts for Indigenous groups in Australia and offer insight for future policy and practice.